Reinterpreting Russia's strategic culture : the Russian way of war - Fasola, Nicolò, 1993- 1993- (Contemporary security studies, 2025)
"This book analyses the categories of thought underpinning Russia's strategic decision-making and military operations, unpacking their nature, development, and interaction. The work argues that mainstream Western analysis of Russian military and strategic behaviour is affected by two limitations: first, by forcing Russian choices into pre-packaged logics of action, it fails to grasp the peculiar assumptions and intellectual nuances underpinning Moscow's strategies; second, an overreliance on buzzwords such as 'hybridity' has mystified understanding of the Russian military modus operandi, its true character and strong consistencies. The book addresses such limitations by stressing the influence of strategic culture on Russia's approach to strategy and war-fighting. After proposing an original model of strategic culture, it employs this conceptual framework to interrogate Russian primary sources and military practices between 2008 and 2018. This allows general hypotheses to be formulated about the ultimate principles underpinning the Russian way of war, which are then tested against three case studies: Russia's interventions in Georgia (2008), Ukraine (2014-15), and Syria (2015-18), respectively. While steering clear of making forecasts, this book provides a solid basis on which to build expectations about and to chart strategies for counter-acting Moscow's actions - including in the context of the current war in Ukraine. This book will be of much interest to students of Russian security, military and strategic studies, foreign policy and International Relations in general."